A phenomenological investigation of the experience of "connected breathing" - Van Wyk, Edmund (Rhodes University, Faculty of Humanities, Department of Psychology, 1983)
My interest in "Connected Breathing" began with my own experience of this technique during a Gestalt workshop. It had a profound impact on me. I knew practically nothing about the theory, or lack of a theory, but my interest had been aroused. In my reading on the subject later, I was struck by the incongruence between my experience and what I read I was supposed to be experiencing. This led me "zu der Sache selbst." By using the phenomenological method, this study then is an attempt to come to an essential description of the experience of "Connected Breathing" and to make some evaluation of its usefulness as a psychotherapeutic technique. "Connected Breathing" is the main technique of the "Rebirthing" movement. It is, therefore, necessary to give some account of the development and theory, if any, of this movement. "Rebirthing" does not claim to be a psychotherapy. However, its technique of "Connected Breathing" does seem to have much in common with the techniques used by various established somatic psychotherapies. A brief overview of the development of some of these psychotherapies and their emphasis on breathing techniques is, therefore, also essential.
Keywords: Uncatalogued